2014
DOI: 10.1186/1471-2164-15-774
|View full text |Cite
|
Sign up to set email alerts
|

Identification of male-specific amh duplication, sexually differentially expressed genes and microRNAs at early embryonic development of Nile tilapia (Oreochromis niloticus)

Abstract: BackgroundThe probable influence of genes and the environment on sex determination in Nile tilapia suggests that it should be regarded as a complex trait. Detection of sex determination genes in tilapia has both scientific and commercial importance. The main objective was to detect genes and microRNAs that were differentially expressed by gender in early embryonic development.ResultsArtificial fertilization of Oreochromis niloticus XX females with either sex-reversed ΔXX males or genetically-modified YY ‘super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 69 publications
3
129
1
2
Order By: Relevance
“…In fact, high doses of E 2 treatment are needed to induce complete male to female sex reversal in rainbow trout, tilapia and other teleosts (Krisfalusi & Nagler 2000, Bhandari et al 2005, Gennotte et al 2014. This might be explained by the following two possible reasons: i) though the ovarian differentiation occurs earlier than testicular differentiation, the male determining gene, such as amhy in tilapia, expresses even earlier than the female pathway genes (Eshel et al 2014, Li et al 2015a, and therefore high doses of E 2 are needed to antagonize the male pathway genes, which is further supported by the differential sensitivity of XY and YY genotypes to embryonic induced-feminization (Gennotte et al 2014); and ii) almost all steroidogenic enzyme genes are expressed in XX gonads but not in XY gonads at 5 dah (Tao et al 2013), and therefore high doses of E 2 are needed to induce those genes, especially cyp19a1a, expression for ovarian differentiation. Signals of Dmrt1 and Cyp19a1a could be simultaneously detected at 10 dah in the MT-XX gonad while Cyp19a1a disappeared latter on.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, high doses of E 2 treatment are needed to induce complete male to female sex reversal in rainbow trout, tilapia and other teleosts (Krisfalusi & Nagler 2000, Bhandari et al 2005, Gennotte et al 2014. This might be explained by the following two possible reasons: i) though the ovarian differentiation occurs earlier than testicular differentiation, the male determining gene, such as amhy in tilapia, expresses even earlier than the female pathway genes (Eshel et al 2014, Li et al 2015a, and therefore high doses of E 2 are needed to antagonize the male pathway genes, which is further supported by the differential sensitivity of XY and YY genotypes to embryonic induced-feminization (Gennotte et al 2014); and ii) almost all steroidogenic enzyme genes are expressed in XX gonads but not in XY gonads at 5 dah (Tao et al 2013), and therefore high doses of E 2 are needed to induce those genes, especially cyp19a1a, expression for ovarian differentiation. Signals of Dmrt1 and Cyp19a1a could be simultaneously detected at 10 dah in the MT-XX gonad while Cyp19a1a disappeared latter on.…”
Section: Discussionmentioning
confidence: 99%
“…Despite having a strong TSD, another pejerrey, O. bonariensis, also expressed amhy at early stages of male promoting temperatures followed by the expression of the autosomal amha gene, showing the coexistence of both temperature and genetic sex determination in this species [Yamamoto et al, 2014]. Two tandem Y copies of the amh gene have been identified in the Nile tilapia with a 233-bp deleted region in exon VII and a 5-bp insertion in exon VI that leads to a truncated amh gene lacking the TGF-β domain [Eshel et al, 2014;Li et al, 2015], defined as amhΔY, and another amhy having a missense SNP which may be determining sex in some strains, notably the Japanese strain [Li et al, 2015]. In several pufferfish (Takifugu) species an allelic variation in the amhr2 gene, the amh receptor, has been shown to be responsible for maleness [Kamiya et al, 2012].…”
Section: New Actors Of Sex Determination and Differentiationmentioning
confidence: 99%
“…In the Nile tilapia the 233-bp deleted amh gene, which was initially called amhy [Eshel et al, 2014] and later amhΔY [Li et al, 2015], was identified in males and considered to be specific for the Y chromosome and was always associated to the male sex determinant amhy in this species. We analyzed the existence of the amhΔY in different sexual genotypes of the domesticated Manzala strain using primers that covered both the deleted and undeleted regions of the amh genes producing a fragment of 800 bp and 1,000 bp.…”
Section: Sex Reversal In the Wildmentioning
confidence: 99%
See 2 more Smart Citations